Subsurface drip irrigation mitigated greenhouse gas emission and improved root growth and yield in apple in semi-arid region - Liu, Jiabin; Gao, Xiaodong; Song, Juanjuan; Wen, Mingyi; Wang, Jianjun; Cai, Yaohui; Zhao, Xining (Agricultural water management, 2025)
Irrigation is the dominating strategy for achieving high yields and has a direct impact on greenhouse gas (GHG) emissions. As a result, optimizing irrigation methods is crucial for improving apple yield and resilience to drought while also diminishing greenhouse gas emission intensity (GHGI). However, the impact of changes in drip irrigation methods on GHG emissions, apple yield and drought resistance is unclear. We conducted a two-year field experiment to research the effects of surface drip irrigation (DI), subsurface drip irrigation (SDI), and no irrigation (CK) on soil GHG emissions (CH4, CO2, N2O), as well as the regulatory mechanisms of yield and root growth (root length density, diameter) in apple orchards. The results indicated that, compared to DI treatment, SDI treatment significantly (p < 0.05) increased apple yield by 29.37–37.97 % and augmented root length density in deeper soil layers, especially in the 20–40 cm layer, where root length density increased by 70.0 %. Moreover, in comparison to DI treatment, SDI could decrease the cumulative CO2 emission flux by 5.34–6.53 %, decrease the cumulative N2O emission flux by 14.41–18.51 %, enhance the cumulative CH4 absorption flux by 14.82–26.51 %, and considerably (p < 0.05) lower GHGI by 29.41–31.58 %. The correlation analysis results indicated a positive association between soil moisture and GHG emissions, with the most significant impact noted in the surface soil layer (0–20 cm). In contrast, increased soil moisture at depths of 40–80 cm was found to inhibit apple root length density. In summary, SDI can enhance apple yield, foster deep root development, and reduce GHG emissions. The research findings offer empirical evidence for the sustainable growth and ecological preservation of the apple industry. [Display omitted] •Subsurface drip irrigation promoted the development of deep roots and improved the drought resilience of apple.•Subsurface drip irrigation reduced the cumulative emission fluxes of CO2 and N2O.•Subsurface drip irrigation significantly increased apple yield and reduced GHGI.